Matches and mismatches between EFL teachers’ and students’ preferences for corrective feedback in English speaking classes: A study at a Vietnamese university - Lưu, Thị Hương (2020)
The author carries out this study to aim at examining teachers’ and students’ preferences regarding different types of corrective feedback in EFL speaking classrooms at Hanoi Pedagogical University 2 (HPU2), Vietnam. In order to figure out results, the researcher observed 5 classes to identify the currently implemented corrective feedback strategies that are preferred by HPU2’s teachers. Additionally, the study examines the students’ and teachers’ differences in preferences regarding corrective feedback strategies. The matches or mismatches between teachers’ and students’preferences for oral corrective feedback are the emphases for this investigation.